PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD 101874 BATANG KUIS - Syahbudin Syahbudin (JURNAL TEMATIK, 2018)
The purpose of this research is to know: (1) problem of learning media on problem learning in mathematics (2) the feasibility of problem-based learning media on the learning of flat matter mathematics, and (3) the effectiveness of problem-based learning video media on learning mathematics of flat wake matter in class V in SD Negeri 101874 Kabupaten Deli Serdang. The subjects of this study are the students of grade V SD Negeri 101874 Batang Kuis with a total of 30 students. This type of research is development research using Thiagarajan development model with Four-D (Model 4-D). The research instruments used were expert opinion questionnaire, student response questionnaire, teacher response questionnaire, and student learning result test instrument. The research findings show: (1) valid problem-based learning video used in learning mathematics of flat wake material in class V SD Negeri 101874 Batang Kuis Kabupaten Deli Serdang, (2) problem-based learning video suitable for learning mathematics of flat wake material in class V SD Negeri 101874 Batang Kuis Kabupaten Deli Serdang, and (3) problem-based learning videos are effectively used in learning mathematics of flat waking materials in class V SD Negeri 101874 Batang Kuis Kabupaten Deli Serdang.